MAGNITUDE OF HETEROSIS FOR POD YIELD AND ITS CONTRIBUTING CHARACTERS IN OKRA [ABELMOSCHUS ESCULENTUS (L.) MOENCH] - HIMANI B. PATEL,; D. R. BHANDERI,; A. I. PATEL,,; R. V. TANK,; AKHILESH KUMAR, (The Bioscan, 2015)
24 F1 hybrids from eight lines and three testers were evaluated with the objective of identifying the high yielding parents and F1 hybrids through Line x Tester mating design to estimate the heterosisduring Summer-2014.The genotypes differed significantly for most of the characters studied. Theheterosiswas recorded for pod yield and its 14 component characters. As a result, three F1 hybrids, AOL 10 - 22 x VRO-6, JOL 09 - 05 x GAO - 5 and AOL 09 - 02 x VRO-6 recorded high degree of heterosis for yield and its contributing characters. High estimates of heterosis obtain in hybrid combinations revealed considerable genetic divergence among the parental lines.